2019
DOI: 10.7150/jca.29216
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic lymph node ratio as a prognostic indicator in patients with stage IV colon cancer undergoing resection

Abstract: Background : It has been shown that the metastatic lymph node ratio (LNR, metastatic LNs divided by the total number of retrieved LNs) significantly affects the prognosis of patients with non-stage IV and some curative stage IV colon cancer undergoing curative resection. In this study, we aimed to evaluate the role of the LNR as a predictor of prognosis in patients with stage IV colon cancer undergoing curative or palliative resection. Patients and Methods : We conducted a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
3
12
0
Order By: Relevance
“…Based on our multivariate analysis, tumor size was also an independent factor for improved OS (HR 1.17, 95% CI 1.01-1.37, P = 0.038), which was in agreement with previous reports [23][24][25][26]. Previous researches have revealed that a high lymph node ratio (LNR) was significantly correlated with inferior overall and disease-free survival in stage III [27][28][29] and stage IV [30][31][32] colorectal cancer patients, which is in line with this study.…”
Section: Discussionsupporting
confidence: 91%
“…Based on our multivariate analysis, tumor size was also an independent factor for improved OS (HR 1.17, 95% CI 1.01-1.37, P = 0.038), which was in agreement with previous reports [23][24][25][26]. Previous researches have revealed that a high lymph node ratio (LNR) was significantly correlated with inferior overall and disease-free survival in stage III [27][28][29] and stage IV [30][31][32] colorectal cancer patients, which is in line with this study.…”
Section: Discussionsupporting
confidence: 91%
“…The role of LNR in CRC was initially studied by Berger et al in 2005 [ 231 ]. LNR has been reported as a negative independent prognostic indicator in stage III and IV CRC and is associated with reduced OS and DFS [ 33 , 44 , 229 , 230 , 232 , 233 , 234 , 235 ]. A systematic review and meta-analysis by Ceelen et al in 2010 reported a pooled HR of 2.36 for OS and 3.71 for DFS in stage III CRC patients with a high LNR [ 230 ].…”
Section: Pathological Featuresmentioning
confidence: 99%
“…The prognostic significance of LNR may be greater when there is a lymph node yield <12 [ 44 , 236 ]. Evidence for LNR as an independent prognostic factor is strongest in stage III CRC, however evidence for stage IV CRC is also robust [ 33 , 229 , 233 ].…”
Section: Pathological Featuresmentioning
confidence: 99%
“…Berger et al first reported the prognostic role of mLNR in CRC [16], though no detailed information regarding the criteria for high mLNR is currently available. Recently, the mLNR has been explored as a prognostic factor on survival outcomes and time to progression for patients with colon cancer [17,18,19,20,21,22,23,24,25,26].…”
Section: Introductionmentioning
confidence: 99%